Feeling secure vs. being secure? Qualitative evidence on the relationship between labour market institutions and employees' perceived job security from Germany and the U.S. - Lena Hipp (Contemporary Social Science, 2020)
How can labour market institutions make workers confident about their economic future? While quantitative studies have repeatedly shown that countries' labour market regulations and policies are related to variations in workers' perceived job security, these studies did not explain how these institutions affect workers' perceptions and expectations. This study seeks to close this gap by analysing qualitative interview data collected on employees in Germany and the U.S. during the great financial crisis (2009–2010). The study's main finding is that policies vary in their effectiveness at making workers feel secure about their jobs. While unemployment assistance can reduce workers' worries about job loss, dismissal protection does not seem to effectively increase workers' confidence that their jobs are secure. Overall, employees know relatively little about the policies and regulations that are meant to protect them and have limited trust in their effectiveness. Individual and organisational characteristics seem to be more relevant for employees' feelings of job security than national-level policies. In particular, comparisons with others who have lower levels of protection increase workers' perceived security. These insights are particularly important in light of the ongoing changes in the world of work that are making workers' lives more uncertain and insecure.
Keywords: 330; perceived job insecurity/security; U.S. and Germany; labour markets policies; institutions